Demographic characteristics and health behaviours of consenters to medical examination. Results from the Welsh Heart Health Survey. Issue 4 (August 1992) - Pullen, E; Nutbeam, D; Moore, L
Abstract : STUDY OBJECTIVE--The aim was to compare the demographic characteristics and health related behaviours of people who consented to a medical examination as part of a population survey with those who did not. STUDY DESIGN--The study formed part of the (1985) Welsh Heart Health Survey, which comprised a three stage design involving household interview, self completion questionnaire, and medical examination. Subjects for medical examination were selected from responders to the questionnaire survey (67%). Sixty six per cent of this group consented to medical examination (n = 11, 637). Odds ratio analysis techniques were used to compare consenters and non-consenters. MEASUREMENTS AND MAIN RESULTS--The analysis was based on self reported information available from previously completed questionnaires, and from personal interviews. The study supported the findings of previous research indicating that consenters to medical examination are more likely to be from non-manual social groups, to be aged 25-44 years, to be educated beyond school age, and to be married. Individuals with healthy lifestyle characteristics (diet, physical activity) were overrepresented among consenters. The only exception to this finding was in relation to excessive alcohol consumption. CONCLUSIONS--These findings emphasise the importance of maximising response rates in all forms of social research including surveys with a clinical component. They also have methodological and analytical implications for the Welsh Heart Health Survey.